Testing Interscience in Understanding and Tackling Disaster Risk - Bwambale, Bosco; Kervyn, Matthieu (Frontiers in Earth Science, 2021)
Efforts in Disaster Risk Reduction (DRR) are widely geared towards integrating indigenous knowledge and science. Several conceptual frameworks have thus evolved towards co-creating knowledge and co-designing DRR measures from the standpoint of the communities-at-risk. This is claimed to foster optimization and sustainability of measures. This study tests the effectiveness of this standpoint argument based on the case of floods in the Rwenzori, western Uganda, where a mismatch is noted between research, policy, and action. A protocol was developed to stimulate dialogue on knowledge co-creation and co-designing of DRR measures among participants from three stakeholder groups: scientists, policymakers, and communities-at-risk. Beyond convergence on some measures among participants, equitable deliberations were observed among the different stakeholders. This enabled three processes: coalescing some of the proposed measures, the emergence of hybrid worldviews, and co-design of alternative options. The co-designed options fall within the contemporary conceptualization of nature-based solutions and sustainability. This meant that they are adoptable and optimizable over time by communities-at-risk. This constructive knowledge integration and co-design of DRR options were favored by three attributes: coalescing overlaps in theorizations of processes, embracing diversity in ontological values, and self-critiques among policymakers. Lessons are drawn on how these attributes facilitate bridging gaps between science, policy, and action in DRR.